Pendampingan Perhitungan Proyeksi Keseimbangan Air Perusahaan Daerah Air Minum Tirta Sembada Unit Tridadi Sleman - Titek Widyasari; Hari Susanto; Tania Edna Bhakty; Nizar Achmad (Yayasan Literasi Sains Indonesia, 2025)
PDAM Tirta Sembada Tridadi Unit in Sleman faces challenges in ensuring the sustainability of clean water services due to a potential imbalance between water supply and demand in the future. This community service activity aimed to provide technical assistance in calculating the projected water balance for the 2024–2034 period. The geometric method was applied using existing data on water availability and demand. The analysis revealed a decreasing trend in water availability from 14,2 L/s to 9,2 L/s, while water demand increased from 6,1 L/s to 9,2 L/s. A critical point is projected to occur in 2034, as water demand is anticipated to equal available supply, thereby posing a risk of water deficit if no immediate measures are taken. It improved the technical understanding of PDAM staff regarding the application of projection methods and analysis of water balance graphs. The recommended follow-up actions include diversifying water sources, improving distribution efficiency, and increasing public awareness of water conservation. The outcomes of this activity are expected to support long-term planning for sustainable water provision.